Evaluation of Material Sustainability Using Analytical Hierarchy Process - Sunil Thakare, Dr. Satish S. Deshmukh, Vaishnavi Chidrawar, Gajanan Mandaware (Mathematical Statistician and Engineering Applications, 2021)
Sustainability and sustainable construction became integral part in reducing impact on social, economic and environmental aspects in developed and developing countries. To achieve sustainability in construction, selection of material plays an important role. As construction industry largely depends on resources and hence material selected should follow all the principles of sustainability. Comprehensive review of methods for selecting construction material is carried out and found that very few studies are available for deciding the alternatives for binder material, fine aggregate and coarse aggregate for sustainability. The sustainable score is then taken as an input to Analytical Hierarchy Process and statistical analysis is carried out to determine the best material among the available alternatives for the three ingredients of concrete.